Antibiotic resistance of Helicobacter pylori in Chinese children: A multicenter retrospective study over 7 years. Issue 3 (18th January 2017) - Li, Lan; Ke, Yini; Yu, Chaohui; Li, Guogang; Yang, Ningmin; Zhang, Jianzhong; Li, Youming
Abstract: Background: To determine the prevalence of resistance to metronidazole, clarithromycin, levofloxacin, amoxicillin, and furazolidone in Helicobacter pylori isolated from Chinese children. Materials and Methods: This multicenter retrospective study was conducted from January 2009 to December 2015. A total of 1746 isolates of H. pylori were collected from nine areas of Zhejiang province in the southeast coastal region of China. H. pylori strains were examined for antibiotics susceptibility by agar dilution method. Results: The resistance rates were 75.20% for metronidazole, 16.38% for clarithromycin, 6.70% for levofloxacin, 0.06% for amoxicillin, and 0.06% for furazolidone. The pattern of H. pylori antibiotic resistance demonstrated no significant changes in the rates of resistance to clarithromycin, amoxicillin, furazolidone, and metronidazole over 7 years. A significant trend of increasing resistance to metronidazole was observed as children aged, but a downward trend in clarithromycin resistance was observed as children aged. No difference in the resistance to other antibiotics was observed among different age groups. Also, there was no significant difference between male and female subjects in rates of resistance to these five types of antibiotics. The predominant dual resistance to metronidazole and clarithromycin was presented in 10.65% of the isolates. Conclusions: The resistance rates of H. pylori in children from southeast coastal region of China were very high to metronidazole, moderate to clarithromycin and levofloxacin, and low to amoxicillin and furazolidone. It is important to continue monitoring the resistance profiles of H. pylori isolated in this region.